Interactions between Two Herbivores Introduced as Biocontrol Agents against Invasive Purple Loosestrife - Torreblanca, Marina (Université d'Ottawa / University of Ottawa, 2017)
Theory predicts that, upon release from natural enemies in the new range, invasive species will evolve to allocate more resources towards traits that improve their ability to compete with native species. The motivation for most biological control programs is to re-introduce native enemies in order to oppose this effect and reduce or even reverse some of the negative impacts of invasive species on native and economically important ecosystems. In many cases, multiple biocontrol agents are introduced, often under the assumption that their impacts will be complementary. However, studies that attempt to quantify the nature of interactions among biocontrol agents tend to find unique outcomes: as yet, no general patterns have emerged. Here I describe the findings of a study of the impacts of the introduction of one species of biocontrol agent of invasive purple loosestrife, the leaf beetle Neogalerucella almariensis, on the reproductive success of a second biocontrol agent, the flower-feeding weevil Nanophyes marmoratus. Somewhat surprisingly, I found that more adult weevils tended to emerge from plants that were simultaneously infested with both types of beetles. This was true even when differences in flower number among plants were taken into account. Moreover, there were more aborted flowers on an inflorescence where both biocontrol agents were present. Finally, more pollinators visited the plants that were infested by both biocontrol agents. The observational data also show a positive correlation between the presence of the leaf beetle larvae and the number of adult flower weevils found on an inflorescence. I discuss various explanations, including the possibility that biocontrol-induced changes in flowering phenology and plant nutritional compounds could be, at least partially, responsible for these findings.
Keywords: biocontrol; purple loosestrife; herbivore; interaction